LINGUOCOGNITIVE MODELS IN TRANSLATION: A MULTIDIMENSIONAL APPROACH - Mukhammedova Mokhinur Bakberganovna (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Abstract: Translation is a cognitively complex process that involves not only linguistic transformation but also mental conceptualization. Linguocognitive models play a vital role in shaping how translators perceive, interpret, and render meaning between languages. These models, which include frame semantics, conceptual metaphor theory, and cognitive load theory, help explain how meaning is stored and accessed in the mind. This paper investigates how such models influence the translator’s choices, particularly when dealing with culturally loaded or figurative expressions. By analyzing English-Uzbek translation samples, the research illustrates how linguocognitive awareness contributes to improved accuracy, contextual appropriateness, and cultural sensitivity in translation.